The characteristics of training periods to the podium in Olympic medalists - Kojima, Y.; Hagiwara, M.; Kinugasa, T. (Journal of High Performance Sport, 2022)
It has been known that athlete development pathway is a long-term process determined by a complex interplay of various factors and elements of athlete development. It is important to develop athletes holistically and systematically for improving international competitiveness. Understanding the age of peak performance of elite athletes could provide important information for long-term development and high performance strategic planning. The aim of this study was to estimate training periods of Rio de Janeiro 2016 Summer Olympic Games and PyeongChang 2018 Winter Olympic Games medalists (n=1,471) based on the sports categorization (cgs, artistic, combat, game, target, and others) by analyzing the starting age of main sport and age of winning the first medal at Olympic Games. The data suggest that the characteristics of Olympic medalists were as follow: (1) the lower the starting age, the longer the training period, and the higher the starting age, the shorter the training period; (2) the starting age was higher and the training period was shorter in the cgs sports compared with other sports; and (3) the starting age was lower and the training period was longer in the artistic and game sports compared with the other sports.